Optical detection and spatial modulation of mid-infrared surface plasmon polaritons in a highly doped semiconductor - Di Paola, D.M.; Velichko, Anton V.; Bomers, Mario; Balakrishnan, Nilanthy; Makarovsky, Oleg; Capizzi, Mario; Cerutti, Laurent; Baranov, Alexei N.; Kesaria, M.; Krier, A.; Taliercio, Thierry; Patanè, Amalia (Wiley, 2018)
Highly doped semiconductors (HDSCs) are promising candidates for plasmonic applications in the mid-infrared (MIR) spectral range. This work examines a recent addition to the HDSC family, the dilute nitride alloy In(AsN). Post-growth hydrogenation of In(AsN) creates a highly conducting channel near the surface and a surface plasmon polariton detected by attenuated total reflection techniques. The suppression of plasmonic effects following a photo-annealing of the semiconductor is attributed to the dissociation of the N-H bond. This offers new routes for direct patterning of MIR plasmonic structures by laser writing.